Nietzsche and phenomenology - Rehberg, Andrea (Cambridge Scholars Publishing, 2011)
This collection brings together original essays on a wide variety of topics in the broad area of Nietzsche and phenomenology. Some of these papers take a thematic approach, thinking through key issues that connect or divide Nietzsche and phenomenology.
Keywords: Nietzsche, Friedrich Wilhelm, -- 1844-1900 -- Criticism and interpretation.; Nietzsche, Friedrich Wilhelm, -- 1844-1900; Phenomenology.; Phénoménologie.; phenomenology.; History of Western philosophy.; Phenomenology & Existentialism.; Deconstructionism, Structuralism, Post-structuralism.; PHILOSOPHY -- History & Surveys -- Modern.; Phenomenology; Criticism, interpretation, etc.